The heritage obsession: The history of rock and challenges of ‘museum mummification’: A French perspective - Le Guern, Philippe (Popular Music History, 2017)
This article considers the particular shape of popular music heritagization in French archives, museums and broader culture. Drawing on Derrida’s Archive Fever and Huyssen’s notion of heritage obsession, the article asks what has encouraged the rapid growth of pop and rock heritage in general, before examining a number of case studies in Paris, Laval and Avignon to build up a picture of French museum practices towards popular music heritage. Specifics of French policy and culture such as the Fédurok agency are explained, and the contrasts between AngloAmerican and French treatments of popular music heritage are delineated, with Francophone experience defined precisely by its differences from this established reading. Thus, in providing a sociological model for understanding the rock music heritage obsession in France, it is those cases that fall outside of the canonical understanding of rock music such as bal-musette that are argued to be key to French popular music heritage.